2014
DOI: 10.1159/000365794
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Micronutrient Needs in Pregnancy in Industrialized Countries

Abstract: Background: As nutritional deficiencies are known to lead to adverse pregnancy outcomes, a woman's nutritional status should be assessed preconceptionally with the goal of optimizing maternal, fetal and infant health. Worldwide micronutrient intakes do not fit pregnancy requirements, so that their supplementation is recommended from the beginning of pregnancy in most of the low- and middle-income countries. Conversely, data on multiple supplementation in developed countries appear few and controversial. Key Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 56 publications
2
42
0
Order By: Relevance
“…2) [6,17,33]. Even in developed countries, where a balanced diet is accessible, micronutrient inadequacies are common due to a general switch to high-fat and low-quality diets (e.g., in highly processed products rich in salt, sugar and saturated fats), with frequently suboptimal intake particularly of iron, iodine, folate, vitamin D, vitamin B 12 and docosahexaenoic acid (DHA) [33,34].…”
Section: Nutrient Supply and Early Programmingmentioning
confidence: 99%
See 1 more Smart Citation
“…2) [6,17,33]. Even in developed countries, where a balanced diet is accessible, micronutrient inadequacies are common due to a general switch to high-fat and low-quality diets (e.g., in highly processed products rich in salt, sugar and saturated fats), with frequently suboptimal intake particularly of iron, iodine, folate, vitamin D, vitamin B 12 and docosahexaenoic acid (DHA) [33,34].…”
Section: Nutrient Supply and Early Programmingmentioning
confidence: 99%
“…2) [6,17,33]. Even in developed countries, where a balanced diet is accessible, micronutrient inadequacies are common due to a general switch to high-fat and low-quality diets (e.g., in highly processed products rich in salt, sugar and saturated fats), with frequently suboptimal intake particularly of iron, iodine, folate, vitamin D, vitamin B 12 and docosahexaenoic acid (DHA) [33,34]. It is known that low intakes of these micronutrients are of significant clinical relevance in pregnant women because they can lead to health problems in the mother and foetus/newborn [6,28,35].…”
Section: Nutrient Supply and Early Programmingmentioning
confidence: 99%
“…2 Appropriate maternal nutrition should consider intake not only of macronutrients (e.g., proteins, carbohydrates, and fats) but also of micronutrients (e.g., iron, folate, and iodine), for which it may be easier to incur deficiencies or inadequacies [3,99,310]. Importantly, obese women may have important nutritional deficiencies [3].…”
Section: Consensus Recommendationsmentioning
confidence: 99%
“…Maternal health and nutrition are important determinants of healthy pregnancies and impact kidney development [15,99]. These factors are strongly impacted by socioeconomic and structural factors [65,100] (Table 5).…”
Section: Introduction To a Health Problemmentioning
confidence: 99%
“…However, in medium- to high-income countries, it is indicated that there is currently insufficient evidence to support a routine supplementation at the population level, except for periconception folate supplementation, and for most pregnant women, a more individualised approach is recommended with a specific focus on iron, calcium and vitamin D status [3]. …”
mentioning
confidence: 99%